The methods of professional tennis returns with implications for successful returns, return aces and receivers winning - Tashiro, S.; Nakamura, K.; Murakami, S.; Takahashi, H. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: A previous study found that the percentage of break points won was the most determining factor for winning the match in tennis [1]. Furthermore, another study indicates that return points won were among the variables that set high-level players apart from low-level players [2]. Now, the question is: what are the key factors for winning points when returning a serve? This study aims to identify crucial variables that contribute to the receiver`s winning points, as well as successful returns and return aces. METHODS: This study examined 5249 points in 18 right-handed professional mens tennis matches at the US Open between 2019-2021. The direction of the split-step hop, the types of spins and ground strokes used, the landing location of returns, the direction of returns, and the time duration of serves and returns were collected from video recordings. Dilated quantification type 2 was used to identify important variables that could contribute to successful returns, return aces, and receiver`s winning points in four conditions (1st serve-returns in the deuce and ad court, and 2nd serve-returns in the deuce and ad court). RESULTS: The types of spins (p<0.01) and the direction of returns (p<0.01) significantly influenced the success rate of returns for each condition. The findings show that returns toward the center of the court led to successful returns, while off-center returns resulted in more return errors. The landing location of returns (p<0.01) significantly contributed to the occurrence of return aces for each condition, and returns that landed on the server`s forehand side increased the likelihood of achieving more return aces. The time duration of returns (p<0.05) significantly affected the receiver`s winning points for the three conditions (1st serve-returns in the deuce and 2nd serve-returns in the deuce and ad court),and a shorter time duration of returns increases receiver`s chance of winning a point. CONCLUSION: The results of the present study suggest that players should target the center of the court and adopt techniques such as a compact swing to avoid off-center impact in return shots. Returns directed to the forehand side increase the chances of winning return aces. A faster speed of return shots or getting inside the court is a good strategy for a shorter time duration of returns that leads to more opportunities to win points for the receiver. 1. Fernández-García, Á, et al., (2019). Differences in competition statistics between winners and losers in male and female tennis players in Olympic Games. German Journal of Exercise and Sport Reseach, 49:313-318 2. Cui, Y, et al., 2017):Effects of experience and relative quality in tennis match performance during four Grand Slams. International Journal of Performance Analysis in Sport, 17(5):783-801.